Social media use and health promoting lifestyle: an exploration among Indian nursing students - Maya Sahu; Sailaxmi Gandhi; Manoj Kumar Sharma; P. Marimuthu (Universidad de Antioquia, 2020)
Objective. To evaluate the use of social media and the health promoting lifestyle profile of indian nursing students. Methods. A cross-sectional study was carried out with 125 students (89 undergraduate and 36 graduate) from various Nursing universities in India, who provided information on their sociodemographic data, the Bergen Social Media Addiction Scale (BSMAS) and the Health Promoting Lifestyle Profile (HPLP-II). Results. Regarding the BSMAS, the participants had an average of 12.8 (maximum possible = 30); 42% reported they frequently delayed their sleep due to using social media; 9% had excessive use of social media; by gender, men had higher total score than women. With respect to the health promoting lifestyle profile, the total average was 126.9 (maximum possible = 208); no difference was observed by gender in the total score and men scored better in the domain of physical activity; students living with their families had higher scores in the domain of health responsibility than those living alone; and graduate students had better scores than undergraduate students in the scale total and in the domains of health responsibility, spiritual relations, and interpersonal relations. Conclusion. There is excessive use of social media, especially among male students. This study also revealed lower scores than those desired in the domains of Health Promoting Lifestyle, especially for physical activity, health responsibility, stress management, and nutrition. Thereby, the findings may be used to improve health literacy on social media, as well as promote a positive lifestyle among nursing students.